Synthesis and Physiochemical Investigations of Imidazolium 4-Hydroxybenzoate (I4HB) for Nonlinear Optical Applications (Indian Journal of Chemistry (IJC), 2024)
The slow evaporation approach was used to produce and develop imidazolium 4-hydroxybenzoate (I4HB), a novel organic proton-transfer chemical substance. Through single-crystal X-ray diffraction, detailed study showed a monoclinic crystal structure with the centrosymmetric space group P21/n. Vibrational modes were investigated using FTIR and FT-Raman spectra. The chemical structure of the molecule was thoroughly validated using (1H and 13C) NMR analysis. UV-Vis-NIR absorption spectra were used to investigate electronic transitions. Thermal parameters such as a melting point of 215°C and breakdown phases were investigated using TG-DTA analysis. Third-order nonlinearity was also confirmed using Z-scan analysis.